Oxygen effect in Magnetron Sputtered Aluminum doped Zinc oxide films. - Rahmane, Saad; Djouadi, Mohamed Abdou; Aida, Mohamed Salah; Barreau, Nicolas (International Conference on Plasma Surface Engineering, 2013)
In this work, polycrystalline transparent conductive aluminum doped zinc oxide (ZnO:Al) films, have been successfully grown on glass and silicon substrates by rf magnetron sputtering technique at room temperature. The effect of oxygen content in plasma on the structural, optical and electrical properties of the films was systematically studied. The growth rate was fond to decrease with the increase in O2 content. The crystal structure of ZnO:Al films deposited on glass is hexagonal with C axis preferential orientation, while for film deposited on silicon substrate, the preferred orientation of crystallite shifts from (002) to (100) direction with the increase in O2 content. Intrinsic stress increases with an increase of oxygen content, and near stress-free film was obtained at 0 % O2 content. Low resistivity (?= 1.25x10-3 Ocm) associated to high transmittance (T>92 %) in the visible regions, were obtained for ZnO:Al film deposited at room temperature without oxygen content in the deposition chamber. From the optical characterization, we deduced that the band gap shifts towards lower energy with an increase of oxygen content.